Law schools in the 21st century - Guthrie, Rob; Fernandez, Joseph (Legal Service Bulletin Co-Operative Ltd, 2004)
In 2000 the Australian Law Reform Commission (ALRC) report Managing Justice contained a review of legal education. The Commission observed that:The size and structure of the profession as it then existed [in the 1970s] promoted a greater degree of cohesion and solidarity. That position has changed very dramatically over the past three decades. The number of lawyers has grown rapidly … specialisation is now a feature of practice, there are very large national and international firms … the number of law schools has nearly quintupled, and the academy mainly comprised of full time academics has a much more attenuated relationship with the practising profession.1This article examines the change in the delivery of law degrees in the last three decades. We note how legal education has moved away from traditional methods of teaching with a heavy emphasis on substantive law, but includes the study and practice of a range of skills and practices designed to provide a broad legal education. We consider the apparent over-supply of law graduates. We conclude that changes to the legal profession in the last 20 years, which include a reduced availability of clerkships, require a re-thinking of the delivery of law degrees. We argue that the law degree of the 21st century should focus on a student centred approach which integrates increased skills components in order to enhance the employability of the graduates for the legal profession and a range of other professions.